2007
DOI: 10.1577/a06-083.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stress and Dietary Natural‐Source Vitamin E on Nonspecific Immunocompetence, Tissue Tocopherol Composition, and Postslaughter Fillet Oxidative Stability in Sunshine Bass

Abstract: We evaluated the effects of stressor exposure and super‐requirement levels of RRR‐α‐tocopheryl acetate (natural‐source vitamin E [NSVE]) on production performance and nonspecific immunocompetency of juvenile sunshine bass (female white bass Morone chrysops × male striped bass M. saxatilis). Stressor exposure elicited physiological changes consistent with the generalized stress response, and the magnitude of responses generally mirrored stressor severity. Stressor exposure resulted in lower fillet peroxides and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Advanced degradation is signified by an increase in aldehyde concentrations, the byproduct of the oxidation of peroxides (German and Kinsella, 1985).Higher aldehyde concentrations in summer harvested fish suggests that these fish experienced greater perimortem stress and poorer shelf life as a result. This is consistent with the observations of Trushenski and Kohler (2007), in which preslaughter stress was observed to increase fillet aldehyde concentrations after short-term frozen storage in Hybrid Striped Bass (Morone chrysops♀ x M. saxatilis♂). 8 www.…”
Section: Discussionsupporting
confidence: 92%
“…Advanced degradation is signified by an increase in aldehyde concentrations, the byproduct of the oxidation of peroxides (German and Kinsella, 1985).Higher aldehyde concentrations in summer harvested fish suggests that these fish experienced greater perimortem stress and poorer shelf life as a result. This is consistent with the observations of Trushenski and Kohler (2007), in which preslaughter stress was observed to increase fillet aldehyde concentrations after short-term frozen storage in Hybrid Striped Bass (Morone chrysops♀ x M. saxatilis♂). 8 www.…”
Section: Discussionsupporting
confidence: 92%
“…Vitamin E is indispensable for crustacean and plays critical roles in a variety of biochemical and physiological processes, such as protecting biological membranes, lipoproteins and oxidation of polyunsaturated fatty acids (PUFA) (Hamre, 2011). The positive effects of vitamin E on growth performance (Kocabas & Gatlin, 1999) and immune response (Trichet, 2010;Trushenski & Kohler, 2007) have been reported in various vertebrate species. Sufficient vitamin E can improve growth performance and tolerate blood oxidative stress in the red seabream fed oxidized fish oil due to the protection of vitamin E against lipid oxidation (Gao et al, 2012).…”
mentioning
confidence: 99%
“…It plays important roles in various biochemical and physiological processes, including serving as an antioxidant as well as in signal transduction (reviewed by Brigelius-Flohe´et al 2002;Fang et al 2002). In nutrition and physiological research with various aquatic species, vitamin E supplementation has been shown to improve growth performance (Kocabas & Gatlin 1999), enhance immunity (Sealey & Gatlin 2002;Puangkaew et al 2004;Trushenski & Kohler 2007) and restore impaired immunity (Montero et al 1998;Sahoo & Mukherjee 2002), as well as influence neuroendocrine function and reproduction under environmental toxicity (Khan & Thomas 2004). Therefore, vitamin E is an essential micronutrient that may have very important applications for both stock enhancement and commercial/ food fish aquaculture of red drum.…”
mentioning
confidence: 99%
“…Numerous studies have shown that dietary vitamin E can influence immune responses of fish including hybrid striped bass (Sealey & Gatlin 2002;Trushenski & Kohler 2007), gilthead sea bream (Sparus Aurata) (Montero et al 1998); grouper (Epinephelus malabaricus) (Lin & Shiau 2005) and carp, Labeo rohita (Hamilton) (Sahoo & Mukherjee 2002). Vitamin E supplementation also has been shown to enhance respiratory burst of fish macrophages (Blazer 1991;Sealey & Gatlin 2002).…”
mentioning
confidence: 99%